Fabrication of single-axis prosthetic foot using 3d printing and resin infusion method - Rahmatika S, Devi Dwi; Arifvianto, Budi; Dharmastiti, Rini (Jurnal Teknosains, 2025)
A prototype of a single-axis prosthetic foot is proposed as an alternative prosthetic foot for patients with disabilities to perform daily activities. Three leading positions within 0-64% of the gait cycle are heel strike, midstance, and toe-off positions used as boundary conditions. The Finite Element Method can analyze a model to determine the values of deformation, stress, and strain that occur in detail. This research is conducted to fabricate an optimal prosthetic foot product or prototype and determine its strength to support the weight of the user's body and provide comfort and safety before being fabricated using 3D printing and resin infusion methods. The fabrication of the prosthetic foot prototype used Fusion 360 software and continued with simulation testing using ABAQUS 6.14 software. The prototype model was designed and evaluated to obtain strength and feasibility before being fabricated with an Anycubic Photon Mono X type DLP 3D printing machine and resin infusion method. The results obtained in this study show that the prototype of a single-axis prosthetic foot can support the human body's weight with loading level P3 or 60 kg, level P4 or 80 kg, and level P5 or 100 kg according to ISO 10328. The mass of the prototype or single-axis prosthetic foot product is 657 grams, according to the criteria, not more than 1.7% of the user's total body weight, with a hardness value of 55.5 HA, and can withstand 50,000 cycles in fatigue testing.